Vytautas Kubilius: The Relevance of Soviet-Era Hermeneutics - Rubavičius, Vytautas (Colloquia, 2017)
The liberation from the Soviet occupation marked a fundamental shift in Lithuanian life and culture, it is essential that a more explicit picture of the experience of life under Soviet rule be developed. The author of this article explores the kinds of issues that arise when attempting to understand one’s own remembered life, why there are differences in versions of the past – especially between the stories of people remembering that past and those recreating it from documents and others’ accounts. The author draws attention to the fact that drawing out and “writing” the past, especially while attempting to “distance” oneself from it, inevitably opens up important ethical questions around remembering and historical narrative in general. The article stresses the importance, when recalling and studying the recent past, of integrating internal, self-analytical, and external hermeneutic perspectives, of paying attention to the complex ethical issues involved in the interpretation of texts and documents when assessing people’s biographies and behaviors and creating general, evaluative “portraits” of them. In his consideration of the insights contained in the journals of the literary scholar Vytautas Kubilius, an important cultural figure of the recent past, the author of this article comes to the conclusion that no socalled scholarly studies of memory can be free of the ethical dimensions of understanding and self-perception. The article also highlights certain unique aspects of monograph texts about Lithuanian authors and stresses the importance of grasping the particularities of life during the Soviet period in any effort to understand its texts and documents. The article draws the conclusion that awareness of the ethical aspect of hermeneutics instills awareness of the moral aspects of one’s interpretation and the necessity of “checking” one’s interpretation, and especially any moral assessments, against the question: how would I have acted in those circumstances, as I have imagined them, or today’s actual ones?
Keywords: memory; ethics; hermeneutics; remembering; Soviet era; Vytautas Kubilius